2018
DOI: 10.1364/oe.26.020622
|View full text |Cite
|
Sign up to set email alerts
|

Timing and probability of crosstalk in a dense CMOS SPAD array in pulsed TOF applications

Abstract: As the distance between neighboring devices in large CMOS single-photon avalanche diode (SPAD) arrays is reduced for improving the density, increased crosstalk becomes an important issue, limiting the maximum practical fill factor of the array. In this study, the temporal correlation of crosstalk events, as well as the crosstalk probability, and their dependence on parameters, such as the illumination wavelength and intensity, and the distance between SPADs, are investigated via measurement of a ~45%-fill fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The probability for a false detection pair is (1.45±0.16)×10 −3 for nearest neighbor pixel pairs, while the corresponding value for next nearest neighbors is lower by a factor of ∼ 6. Note that these values are well below the typical values reported in the literature for SPAD arrays (∼ 1%) [6,20,28,60], while conventional SiPM detectors usually have higher probabilities of 4 − 20% [43]. Compared to SiPMs, SPAD arrays usually have a smaller capacitance and consequently a smaller charge flowing through the SPAD.…”
Section: Crosstalk Characterizationmentioning
confidence: 64%
See 1 more Smart Citation
“…The probability for a false detection pair is (1.45±0.16)×10 −3 for nearest neighbor pixel pairs, while the corresponding value for next nearest neighbors is lower by a factor of ∼ 6. Note that these values are well below the typical values reported in the literature for SPAD arrays (∼ 1%) [6,20,28,60], while conventional SiPM detectors usually have higher probabilities of 4 − 20% [43]. Compared to SiPMs, SPAD arrays usually have a smaller capacitance and consequently a smaller charge flowing through the SPAD.…”
Section: Crosstalk Characterizationmentioning
confidence: 64%
“…For the detector used here we estimated the photon detection efficiency (PDE), by comparison with an independent EMCCD measurement, to be 42% at 515 nm and 7 V excess bias. While PDE, DCR, dynamic range and afterpulsing are often depicted in the literature, only few works discuss the issue of inter-pixel crosstalk [6,20,28,44,60]. While both afterpulsing and crosstalk generate artificial correlations, afterpulsing artifacts are avoided here altogether by disregarding the autocorrelation of any single detector, as typically done in HBT experiments.…”
Section: Crosstalk Characterizationmentioning
confidence: 99%
“…Recent advances in SPAD technology have yielded high pixel count imagers which enable fast acquisition rates and sensitivity to individual photons (Gyongy et al, 2018). Since there are multiple smallsize receivers close to one another, measures have been taken to reduce the crosstalk between the neighboring receivers (Jahromi, Kostamovaara, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…Jahromi, S et al analyzed the crosstalk problem in SPAD arrays. In order to improve the fill factor in the array, a SPAD array was fabricated using a 0.35 μm CMOS process, and it was found that the photon noise absorbed by the substrate would significantly increase the crosstalk noise [4]. Mahmoudi, H et al proposed a fiber receiver based on a single photon avalanche diode.…”
Section: Introductionmentioning
confidence: 99%
“…Because the dead time caused by the quenching circuit of the single photon avalanche diode will seriously affect the performance of the system, Wang, C et al considered the effect of the dead time and proposed a fast blind union detection (FBUD) algorithm, and the test results show that the algorithm is significantly better than the traditional algorithm [6]. It can be found that various researches on various applications of SPAD have been carried out in [4]- [6]. However, the design of high-performance SPAD devices can fundamentally improve the characteristics of the system.…”
Section: Introductionmentioning
confidence: 99%